Right inguinal hernia with urinary bladder lateroflexion in a domestic shorthair cat - Dwi Utari Rahmiati; Ramadita Aisyah Putri; M Nur Irfan; Azizah Azizah; Nawangsari Ramadhani (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Inguinal hernia is an uncommon condition in cats, but it may lead to significant complications when the urinary bladder is involved. This report describes a case of right inguinal hernia with urinary bladder lateroflexion in an 8-month-old intact female Domestic Shorthair cat presenting with inguinal swelling and dysuria. During in-hospital observation, no urination occurred for over 12 hours. Physical examination revealed a mass in the right inguinal region. Lateral and ventrodorsal projections confirmed herniation of the urinary bladder into the inguinal canal, with deviation and flexion. Surgical correction was performed by herniorrhaphy, involving repositioning the urinary bladder into the abdominal cavity and closure of the hernial ring. Postoperative evaluation showed stable condition, normal urination, and uncomplicated wound healing.